Linear Model for PM Brake Lining Material Wear Behaviour - Istif, Ilyas; Isin, Ovun; Uzunsoy, Erdem; Uzunsoy, Deniz (WALTER DE GRUYTER GMBH, 2010)
This paper presents a linear model for the dry sliding wear behaviour of a PM copper based brake lining material with the addition of MoS2. The model was based on experimental results related to standard pin-on-disk wear tests of the brake material with various MoS2 contents at constant applied load and sliding velocity. The wear load was considered as the input parameter, whereas the wear rate and friction of coefficient as the output parameters. The predicted results were compared with experimental results by simulating a linear process for each MoS2 content of the material, and it was found that the results obtained from such linear process modelling were satisfactory. The results showed that the linear process model represents an useful tool for the prediction of the brake lining material properties, and that it is more effective than time-consuming experimental procedures.
Keywords: FRICTION PERFORMANCE; INGREDIENTS; PREDICTION; Materials Science